High-strength flame-retardant nylon material and preparation method thereof

By combining modified polyamide 4 and glass fiber, high-strength flame-retardant nylon material is prepared, which solves the shortcomings of existing nylon materials in flame retardancy and mechanical properties, and achieves better flame retardant effects and environmental protection performance, which extends the The service life of the material.

CN119241958APending Publication Date: 2025-01-03WUXI CHANGAN POLYMER MATERIAL FACTORY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411465637.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

Existing nylon materials have shortcomings in flame retardancy, high strength and electrical conductivity, which is difficult to meet the demand for high-performance materials in modern industries.

Method used

By combining modified polyamide 4 and modified glass fiber, high-strength flame retardant nylon materials are prepared by high-speed mixing, drying, twin-screw extruder granulation and injection molding of injection molding machines to improve their flame retardant performance and machinery performance.

Benefits of technology

It significantly enhances the flame retardant effect of the material, reduces the release of toxic gases during combustion, improves environmental protection performance, improves adhesion and fluidity during molding, and extends the service life of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119241958A_ABST
    Figure CN119241958A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of polymer nylon materials, and discloses a high-strength flame-retardant nylon material and a preparation method thereof, the high-strength flame-retardant nylon material comprises the following components: 50-80 parts of modified polyamide 4, 15-25 parts of modified glass fiber, 5-15 parts of an initiator, and 1-3 parts of an antioxidant. The preparation method comprises the following steps: S1, adding the modified polyamide 4, the initiator and the antioxidant into a high-speed mixer, and mixing to obtain a primary mixed solution; s2, adding modified glass fibers into the primary mixed solution obtained in the step S1, mixing, and drying to obtain a secondary mixed solution; s3, granulating the dried mixed solution obtained in the step S2 by using a double-screw extruder, and drying to obtain high-strength flame-retardant nylon particles; and S4, carrying out spline injection molding on the high-strength flame-retardant nylon particles obtained in the step S3 by adopting an injection molding machine to obtain the high-strength flame-retardant nylon test sample. Through modification of polyamide 4, the flame retardant effect of the material is enhanced, release of toxic gas in the combustion process is reduced, and the environmental protection performance of the material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer nylon materials, in particular to a high-strength flame-retardant nylon material and a preparation method thereof. Background Art

[0002] Polyamide 4 is a new type of thermoplastic nylon resin material with good thermomechanical properties and chemical stability, as well as good toughness, tensile properties and impact resistance. Among them, the tensile properties and impact resistance are better than those of nylon 66 and nylon 6. In addition, polyamide 4 has a low melting temperature, is easy to process and has good processing adaptability. The potential application areas of polyamide 4 are very wide, including automobiles, electronics, machinery manufacturing, petroleum and chemical industries, and daily necessities. In the automotive field, polyamide 4 can be used to manufacture bearings, gears, chains, brake pads and transmission belts. In the electronics field, it can be used to manufacture wire insulation and electrical components. In the field of machinery manufacturing, it can be used to manufacture bearings, pump parts, cams, piston rings and gaskets. In the petroleum and chemical industry, it can be used to manufacture valves, pipes, storage tanks and reactor components. In addition, polyamide 4 can also be used to manufacture medical devices, tools and parts. Polyamide 4 is soluble in formic acid, dimethylformamide, acetic acid and hexafluoroisopropanol, so it can be made into a film by a solvent method. The branched modified polyamide 4 can also be injection molded under the action of a precision barrel heater at a temperature of 250°C. Under normal conditions, basic physical properties such as heat resistance and strength of materials are the key to evaluating the practicality of materials. The present invention has a very obvious effect in terms of flame retardancy by modifying polyamide 4.

[0003] As an important engineering plastic, nylon has been widely used in machinery, instrumentation, automobiles, and electronic and electrical fields due to its high strength, good dimensional stability and processing performance. However, with the advancement of science and technology and the development of industry, the performance requirements for nylon materials are increasing, especially in terms of flame retardancy, high strength and conductivity. Therefore, the development of a new nylon material with both high strength and excellent flame retardancy has become a hot topic in current research. Summary of the invention

[0004] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a high-strength flame-retardant nylon material and a preparation method thereof. The present invention utilizes the good thermomechanical properties and chemical stability as well as the good toughness, tensile properties and impact resistance of polyamide 4, and modifies it to have good flame retardancy. The high-strength flame-retardant nylon material is prepared by utilizing the lubricity and high toughness of the modified glass fiber.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] A method for preparing a high-strength flame-retardant nylon material comprises the following steps:

[0007] S1. The modified polyamide 4, initiator, antioxidant were added to a high-speed mixer and mixed at a speed of 350 to 500 r / min for 2 to 5 minutes to obtain a preliminary mixed solution;

[0008] S2. The preliminary mixed solution obtained in step S1 is added with modified glass fiber, mixed at a speed of 1000 to 1200 r / min for 3 to 5 minutes, and dried at 100 to 120 ° C for 2 to 4 hours to obtain a secondary mixed solution;

[0009] S3. The mixed solution after drying is pelletized by a twin-screw extruder and dried at 150 to 180 ° C for 2 to 4 hours to obtain high-strength flame-retardant nylon pellets;

[0010] S4. The high-strength flame-retardant nylon pellets obtained in step S3 are subjected to strip injection molding by an injection molding machine to obtain a high-strength flame-retardant nylon material test sample.

[0011] Preferably, the modified polyamide 4 is prepared by the following steps:

[0012] S101. Add 15 to 25 parts of butyrolactam and 20 to 30 parts of polystyrene to a three-necked flask, melt at 100 to 130° C. to obtain a uniform mixed solution, and mechanically stir for 1 to 3 hours;

[0013] S102. Add 1 to 5 parts of 2-chloroethyl ester and 0.5 to 2 parts of 2,3-dichloropropyl ester to the homogeneous mixed solution obtained in step S101, and stir at a speed of 150 to 240 r / min at 75 to 85 ° C;

[0014] S103. Add 0.5 to 2.0 parts of sodium hydroxide as a catalyst for vacuum distillation to remove water in the experimental system;

[0015] S104. Add 0.5 to 2.0 parts of toluene-2,4-diisocyanate as an activator, and obtain a modified polyamide 4 / polystyrene composite material by casting;

[0016] S105. The modified polyamide 4 / polystyrene composite material is crushed, and the polystyrene is washed away with tetrahydrofuran to obtain modified polyamide 4 powder.

[0017] Preferably, in step S103, the pressure of the reduced pressure distillation is 2.33-3.03 kPa, and the temperature is 100-120°C.

[0018] Preferably, in step S104, the casting temperature is 45-55° C. and the casting time is 20-24 hours.

[0019] Preferably, the preparation steps of the modified glass fiber are:

[0020] S201. Add E-glass fiber to deionized water and ultrasonically disperse for 15 to 20 minutes to obtain a glass fiber dispersion;

[0021] S202. The toughening agent, dimethyl silicone oil and anhydrous ethanol are uniformly mixed to obtain a primary mixed solution;

[0022] S203. The glass fiber dispersion is added to the primary mixed solution and mechanically stirred for 10 to 15 minutes, and then ultrasonically dispersed for 15 to 20 minutes to obtain a secondary mixed solution;

[0023] S204. Filter, wash and dry the secondary mixed liquid to obtain modified glass fiber.

[0024] Preferably, the toughening agent is a liquid crystal elastomer.

[0025] Preferably, the mass ratio of the toughening agent, dimethyl silicone oil and anhydrous ethanol is: 2-8: 0.5-3: 20-25.

[0026] Preferably, the initiator is cumene hydroperoxide.

[0027] Preferably, the antioxidant is one or more of 2,6-di-tert-butyl-4-methylphenol, p-phenylenediamine, and didodecanol ester.

[0028] A high-strength flame-retardant nylon material is prepared according to the preparation method of the high-strength flame-retardant nylon material, and comprises the following components in parts by mass: 50 to 80 parts of modified polyamide 4, 15 to 25 parts of modified glass fiber, 5 to 15 parts of initiator, and 1 to 3 parts of antioxidant.

[0029] Compared with the prior art, the present invention has the following beneficial effects:

[0030] 1. The present invention not only enhances the flame retardant effect of the material by modifying polyamide 4, but also reduces the release of toxic gases during the combustion process, thereby improving the environmental performance of the material.

[0031] 2. Since the present invention has excellent performance in flame retardancy, mechanical properties, processability and environmental protection, it has broad application prospects.

[0032] 3. The present invention effectively improves the problems of strong adhesion and poor fluidity of nylon materials during the molding process by modifying the glass fiber, thereby improving the quality of the nylon material, extending the service life, and can also greatly enhance the strength of the prepared nylon material. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 This is a preparation step of a high-strength flame-retardant nylon material of the present invention;

[0034] Figure 2 This is the infrared spectrum of modified polyamide 4, an important component of nylon materials;

[0035] Figure 3 XRD pattern of modified polyamide 4, an important component of nylon material;

[0036] Figure 4 This is the TG curve of modified polyamide 4, an important component of nylon material. DETAILED DESCRIPTION

[0037] The present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0038] See also Figures 1 to 4 , the present invention provides a technical solution:

[0039] Example 1

[0040] A method for preparing high-strength flame-retardant nylon material:

[0041] S1. The modified polyamide 4, cumene hydroperoxide, and 2,6-di-tert-butyl-4-methylphenol were added to a high-speed mixer and mixed at a speed of 350 r / min for 2 minutes to obtain a preliminary mixed solution;

[0042] S2. The preliminary mixed solution obtained in step S1 is added with modified glass fiber, mixed at a speed of 1000 r / min for 3 minutes, and dried at 100 ° C for 2 h to obtain a secondary mixed solution;

[0043] S3. The mixed solution after drying was pelletized by a twin-screw extruder and dried at 150 ° C for 2 h to obtain high-strength flame-retardant nylon pellets;

[0044] S4. The high-strength flame-retardant nylon pellets obtained in step S3 are subjected to strip injection molding by an injection molding machine to obtain a high-strength flame-retardant nylon material test sample.

[0045] In the above process, the modified polyamide 4 is prepared by the following steps:

[0046] S101. Add 15 parts of butyrolactam and 20 parts of polystyrene into a three-necked flask, melt at 130°C to obtain a uniform mixed solution, and stir mechanically for 1h;

[0047] S102. Add 1 part of 2-chloroethyl ester and 0.5 parts of 2,3-dichloropropyl ester to the homogeneous mixed solution obtained in step S101, and stir at a speed of 150 r / min at 75 ° C;

[0048] S103. Add 0.5 parts of sodium hydroxide as a catalyst to remove water by vacuum distillation, the pressure of the vacuum distillation is 2.33 kPa, the temperature is 100 ℃;

[0049] S104. Add 0.5 parts of toluene-2,4-diisocyanate as an activator, and obtain a modified polyamide 4 / polystyrene composite material by casting at a temperature of 45° C. for 20 h;

[0050] S105. The modified polyamide 4 / polystyrene composite material is crushed, and the polystyrene is washed away with tetrahydrofuran to obtain modified polyamide 4 powder.

[0051] In the above process, the preparation steps of the modified glass fiber are:

[0052] S201. Add E-glass fiber to deionized water and ultrasonically disperse for 15 min to obtain a glass fiber dispersion;

[0053] S202. The liquid crystal elastomer, dimethyl silicone oil, and anhydrous ethanol are uniformly mixed in a ratio of 2:0.5:20 to obtain a primary mixed solution;

[0054] S203. The glass fiber dispersion was added to the primary mixed solution and mechanically stirred for 10 minutes, and then ultrasonically dispersed for 15 minutes to obtain a secondary mixed solution;

[0055] S204. Filter, wash and dry the secondary mixed liquid to obtain modified glass fiber.

[0056] Example 2

[0057] A method for preparing high-strength flame-retardant nylon material:

[0058] S1. The modified polyamide 4, cumene hydroperoxide, p-phenylenediamine were added to a high-speed mixer and mixed at 500r / min for 5 minutes to obtain a preliminary mixture;

[0059] S2. The preliminary mixed solution obtained in step S1 is added with modified glass fiber, mixed at a speed of 1200 r / min for 5 minutes, and dried at 120 ° C for 4 hours to obtain a secondary mixed solution;

[0060] S3. The mixed solution after drying was pelletized by a twin-screw extruder and dried at 180 ° C for 4 h to obtain high-strength flame-retardant nylon pellets;

[0061] S4. The high-strength flame-retardant nylon pellets obtained in step S3 are subjected to strip injection molding by an injection molding machine to obtain a high-strength flame-retardant nylon material test sample.

[0062] In the above process, the modified polyamide 4 is prepared by the following steps:

[0063] S101. Add 25 parts of butyrolactam and 30 parts of polystyrene into a three-necked flask, melt at 100°C to obtain a uniform mixed solution, and mechanically stir for 3h;

[0064] S102. Add 5 parts of 2-chloroethyl ester and 2 parts of 2,3-dichloropropyl ester to the homogeneous mixed solution obtained in step S101, and stir at 85°C at a speed of 240 r / min;

[0065] S103. Add 2.0 parts of sodium hydroxide as a catalyst to remove water by vacuum distillation, the pressure of vacuum distillation is 3.03 kPa, the temperature is 120 ℃;

[0066] S104. Add 2 parts of toluene-2,4-diisocyanate as an activator, and obtain a modified polyamide 4 / polystyrene composite material by casting at a temperature of 55° C. for 24 h;

[0067] S105. The modified polyamide 4 / polystyrene composite material is crushed, and the polystyrene is washed away with tetrahydrofuran to obtain modified polyamide 4 powder.

[0068] In the above process, the preparation steps of the modified glass fiber are:

[0069] S201. Add E-glass fiber to deionized water and ultrasonically disperse for 20 min to obtain a glass fiber dispersion;

[0070] S202. The liquid crystal elastomer, dimethyl silicone oil, and anhydrous ethanol are uniformly mixed in a ratio of 8:3:25 to obtain a primary mixed solution;

[0071] S203. The glass fiber dispersion was added to the primary mixed solution and mechanically stirred for 15 minutes, and then ultrasonically dispersed for 20 minutes to obtain a secondary mixed solution;

[0072] S204. Filter, wash and dry the secondary mixed liquid to obtain modified glass fiber.

[0073] Example 3

[0074] A method for preparing high-strength flame-retardant nylon material:

[0075] S1. The modified polyamide 4, cumene hydroperoxide, didodecyl alcohol ester was added to a high-speed mixer and mixed at 400r / min for 3 minutes to obtain a preliminary mixture;

[0076] S2. The preliminary mixed solution obtained in step S1 is added with modified glass fiber, mixed at a speed of 1100 r / min for 4 minutes, and dried at 110 ° C for 3 hours to obtain a secondary mixed solution;

[0077] S3. The mixed solution after drying was pelletized by a twin-screw extruder and dried at 160 ° C for 3 h to obtain high-strength flame-retardant nylon pellets;

[0078] S4. The high-strength flame-retardant nylon pellets obtained in step S3 are subjected to strip injection molding by an injection molding machine to obtain a high-strength flame-retardant nylon material test sample.

[0079] In the above process, the modified polyamide 4 is prepared by the following steps:

[0080] S101. 18 parts of butyrolactam and 23 parts of polystyrene were added to a three-necked flask, melted at 110°C to obtain a uniform mixed solution, and mechanically stirred for 2h;

[0081] S102. Add 2 parts of 2-chloroethyl ester and 1 part of 2,3-dichloropropyl ester to the homogeneous mixed solution obtained in step S101, and stir at a speed of 180 r / min at 70°C;

[0082] S103. Add 1 part of sodium hydroxide as a catalyst to remove water by vacuum distillation, the pressure of vacuum distillation is 2073kPa, the temperature is 110 ℃;

[0083] S104. Add 1 part of toluene-2,4-diisocyanate as an activator, and obtain a modified polyamide 4 / polystyrene composite material by casting at a temperature of 48° C. for 21 h;

[0084] S105. The modified polyamide 4 / polystyrene composite material is crushed, and the polystyrene is washed away with tetrahydrofuran to obtain modified polyamide 4 powder.

[0085] In the above process, the preparation steps of the modified glass fiber are:

[0086] S201. Add E-glass fiber to deionized water and ultrasonically disperse for 17 min to obtain a glass fiber dispersion;

[0087] S202. The liquid crystal elastomer, dimethyl silicone oil, and anhydrous ethanol are uniformly mixed in a ratio of 4:1:22 to obtain a primary mixed solution;

[0088] S203. The glass fiber dispersion was added to the primary mixed solution and mechanically stirred for 12 minutes, and then ultrasonically dispersed for 17 minutes to obtain a secondary mixed solution;

[0089] S204. Filter, wash and dry the secondary mixed liquid to obtain modified glass fiber.

[0090] Example 4

[0091] A method for preparing high-strength flame-retardant nylon material:

[0092] S1. The modified polyamide 4, cumene hydroperoxide, 2,6-di-tert-butyl-4-methylphenol, and didodecanol ester were added to a high-speed mixer and mixed at 450 r / min for 4 minutes to obtain a preliminary mixed solution;

[0093] S2. The preliminary mixed solution obtained in step S1 is added with modified glass fiber, mixed at a speed of 1000 r / min for 3 minutes, and dried at 110 ° C for 3 hours to obtain a secondary mixed solution;

[0094] S3. The mixed solution after drying was pelletized by a twin-screw extruder and dried at 170 ° C for 3 h to obtain high-strength flame-retardant nylon pellets;

[0095] S4. The high-strength flame-retardant nylon pellets obtained in step S3 are subjected to strip injection molding by an injection molding machine to obtain a high-strength flame-retardant nylon material test sample.

[0096] In the above process, the modified polyamide 4 is prepared by the following steps:

[0097] S101. Add 21 parts of butyrolactam and 26 parts of polystyrene to a three-necked flask, melt at 120°C to obtain a uniform mixed solution, and mechanically stir for 2h;

[0098] S102. Add 3 parts of 2-chloroethyl ester and 1.5 parts of 2,3-dichloropropyl ester to the homogeneous mixed solution obtained in step S101, and stir at a speed of 200 r / min at 82°C;

[0099] S103. 1.4 parts of sodium hydroxide were added as a catalyst for vacuum distillation to remove water, the vacuum distillation pressure was 2.83 kPa, the temperature was 115 ° C;

[0100] S104. 1.4 parts of toluene-2,4-diisocyanate were added as an activator, and a modified polyamide 4 / polystyrene composite material was obtained by casting at a temperature of 48° C. for 22 h;

[0101] S105. The modified polyamide 4 / polystyrene composite material is crushed, and the polystyrene is washed away with tetrahydrofuran to obtain modified polyamide 4 powder.

[0102] In the above process, the preparation steps of the modified glass fiber are:

[0103] S201. Add E-glass fiber to deionized water and ultrasonically disperse for 18 min to obtain a glass fiber dispersion;

[0104] S202. The liquid crystal elastomer, dimethyl silicone oil, and anhydrous ethanol are uniformly mixed in a ratio of 4:2:23 to obtain a primary mixed solution;

[0105] S203. The glass fiber dispersion was added to the primary mixed solution and mechanically stirred for 13 minutes, and then ultrasonically dispersed for 18 minutes to obtain a secondary mixed solution;

[0106] S204. Filter, wash and dry the secondary mixed liquid to obtain modified glass fiber.

[0107] Example 5

[0108] A method for preparing high-strength flame-retardant nylon material:

[0109] S1. The modified polyamide 4, cumene hydroperoxide, p-phenylenediamine, didodecyl alcohol ester were added to a high-speed mixer and mixed at 500r / min for 4 minutes to obtain a preliminary mixture;

[0110] S2. The preliminary mixed solution obtained in step S1 is added with modified glass fiber, mixed at a speed of 1100 r / min for 5 minutes, and dried at 120 ° C for 4 hours to obtain a secondary mixed solution;

[0111] S3. The mixed solution after drying was pelletized by a twin-screw extruder and dried at 170 ° C for 4 h to obtain high-strength flame-retardant nylon pellets;

[0112] S4. The high-strength flame-retardant nylon pellets obtained in step S3 are subjected to strip injection molding by an injection molding machine to obtain a high-strength flame-retardant nylon material test sample.

[0113] In the above process, the modified polyamide 4 is prepared by the following steps:

[0114] S101. Add 23 parts of butyrolactam and 28 parts of polystyrene to a three-necked flask, melt at 120°C to obtain a uniform mixed solution, and mechanically stir for 3h;

[0115] S102. Add 4 parts of 2-chloroethyl ester and 1.5 parts of 2,3-dichloropropyl ester to the homogeneous mixed solution obtained in step S101, and stir at a speed of 230 r / min at 84 ° C;

[0116] S103. 1.8 parts of sodium hydroxide was added as a catalyst for vacuum distillation to remove water, the vacuum distillation pressure was 2.93 kPa, the temperature was 110 ℃;

[0117] S104. 1.8 parts of toluene-2,4-diisocyanate was added as an activator, and a modified polyamide 4 / polystyrene composite material was obtained by casting at a casting temperature of 53° C. for 23 h;

[0118] S105. The modified polyamide 4 / polystyrene composite material is crushed, and the polystyrene is washed away with tetrahydrofuran to obtain modified polyamide 4 powder.

[0119] In the above process, the preparation steps of the modified glass fiber are:

[0120] S201. Add E-glass fiber to deionized water and ultrasonically disperse for 18 min to obtain a glass fiber dispersion;

[0121] S202. The liquid crystal elastomer, dimethyl silicone oil, and anhydrous ethanol are uniformly mixed in a ratio of 7:2.5:24 to obtain a primary mixed solution;

[0122] S203. The glass fiber dispersion was added to the primary mixed solution and mechanically stirred for 14 minutes, and then ultrasonically dispersed for 19 minutes to obtain a secondary mixed solution;

[0123] S204. Filter, wash and dry the secondary mixed liquid to obtain modified glass fiber.

[0124] Comparative Example 1

[0125] A method for preparing high-strength flame-retardant nylon material:

[0126] S1. The modified polyamide 4, cumene hydroperoxide, and 2,6-di-tert-butyl-4-methylphenol were added to a high-speed mixer and mixed at a speed of 350 r / min for 2 minutes to obtain a preliminary mixed solution;

[0127] S2. Add E-glass fiber to the preliminary mixed solution obtained in step S1, mix at a speed of 1000 r / min for 3 minutes, and dry at 100 ° C for 2 h to obtain a secondary mixed solution;

[0128] S3. The mixed solution after drying was pelletized by a twin-screw extruder and dried at 150 ° C for 2 h to obtain high-strength flame-retardant nylon pellets;

[0129] S4. The high-strength flame-retardant nylon pellets obtained in step S3 are subjected to strip injection molding by an injection molding machine to obtain a high-strength flame-retardant nylon material test sample.

[0130] In the above process, the modified polyamide 4 is prepared by the following steps:

[0131] S101. Add 15 parts of butyrolactam and 20 parts of polystyrene into a three-necked flask, melt at 130°C to obtain a uniform mixed solution, and stir mechanically for 1h;

[0132] S102. Add 1 part of 2-chloroethyl ester and 0.5 parts of 2,3-dichloropropyl ester to the homogeneous mixed solution obtained in step S101, and stir at a speed of 150 r / min at 75 ° C;

[0133] S103. Add 0.5 parts of sodium hydroxide as a catalyst to remove water by vacuum distillation, the pressure of the vacuum distillation is 2.33 kPa, the temperature is 100 ℃;

[0134] S104. Add 0.5 parts of toluene-2,4-diisocyanate as an activator, and obtain a modified polyamide 4 / polystyrene composite material by casting at a temperature of 45° C. for 20 h;

[0135] S105. The modified polyamide 4 / polystyrene composite material is crushed, and the polystyrene is washed away with tetrahydrofuran to obtain modified polyamide 4 powder.

[0136] Comparative Example 2

[0137] A method for preparing high-strength flame-retardant nylon material:

[0138] S1. Add nylon 6, cumene hydroperoxide, and 2,6-di-tert-butyl-4-methylphenol to a high-speed mixer and mix at 350 r / min for 2 minutes to obtain a preliminary mixed solution;

[0139] S2. The preliminary mixed solution obtained in step S1 is added with modified glass fiber, mixed at a speed of 1000 r / min for 3 minutes, and dried at 100 ° C for 2 h to obtain a secondary mixed solution;

[0140] S3. The mixed solution after drying was pelletized by a twin-screw extruder and dried at 150 ° C for 2 h to obtain high-strength flame-retardant nylon pellets;

[0141] S4. The high-strength flame-retardant nylon pellets obtained in step S3 are subjected to strip injection molding by an injection molding machine to obtain a high-strength flame-retardant nylon material test sample.

[0142] In the above process, the preparation steps of the modified glass fiber are:

[0143] S201. Add E-glass fiber to deionized water and ultrasonically disperse for 15 min to obtain a glass fiber dispersion;

[0144] S202. The liquid crystal elastomer, dimethyl silicone oil, and anhydrous ethanol are uniformly mixed in a ratio of 2:0.5:20 to obtain a primary mixed solution;

[0145] S203. The glass fiber dispersion was added to the primary mixed solution and mechanically stirred for 10 minutes, and then ultrasonically dispersed for 15 minutes to obtain a secondary mixed solution;

[0146] S204. Filter, wash and dry the secondary mixed liquid to obtain modified glass fiber.

[0147] Comparative Example 3

[0148] A method for preparing high-strength flame-retardant nylon material:

[0149] S1. The modified polyamide 4 and the modified glass fiber were added to a high-speed mixer, mixed at a speed of 1000 r / min for 3 minutes, and dried at 100 ° C for 2 h to obtain a mixed solution in the second step;

[0150] S2. The mixed solution after drying is pelletized by a twin-screw extruder and dried at 150°C for 2h to obtain high-strength flame-retardant nylon pellets;

[0151] S3. The high-strength flame-retardant nylon pellets obtained in step S2 are subjected to strip injection molding by an injection molding machine to obtain a high-strength flame-retardant nylon material test sample.

[0152] In the above process, the modified polyamide 4 is prepared by the following steps:

[0153] S101. Add 15 parts of butyrolactam and 20 parts of polystyrene into a three-necked flask, melt at 130°C to obtain a uniform mixed solution, and stir mechanically for 1h;

[0154] S102. Add 1 part of 2-chloroethyl ester and 0.5 parts of 2,3-dichloropropyl ester to the homogeneous mixed solution obtained in step S101, and stir at a speed of 150 r / min at 75 ° C;

[0155] S103. Add 0.5 parts of sodium hydroxide as a catalyst to remove water by vacuum distillation, the pressure of the vacuum distillation is 2.33 kPa, the temperature is 100 ℃;

[0156] S104. Add 0.5 parts of toluene-2,4-diisocyanate as an activator, and obtain a modified polyamide 4 / polystyrene composite material by casting at a temperature of 45° C. for 20 h;

[0157] S105. The modified polyamide 4 / polystyrene composite material is crushed, and the polystyrene is washed away with tetrahydrofuran to obtain modified polyamide 4 powder.

[0158] In the above process, the preparation steps of the modified glass fiber are:

[0159] S201. Add E-glass fiber to deionized water and ultrasonically disperse for 15 min to obtain a glass fiber dispersion;

[0160] S202. The liquid crystal elastomer, dimethyl silicone oil, and anhydrous ethanol are uniformly mixed in a ratio of 2:0.5:20 to obtain a primary mixed solution;

[0161] S203. The glass fiber dispersion was added to the primary mixed solution and mechanically stirred for 10 minutes, and then ultrasonically dispersed for 15 minutes to obtain a secondary mixed solution;

[0162] S204. Filter, wash and dry the secondary mixed liquid to obtain modified glass fiber.

[0163] Performance testing and result analysis:

[0164] The high-strength flame-retardant nylon material test samples prepared in Examples 1 to 5 and Comparative Examples 1 to 3 were subjected to mechanical property tests. The test standards are as follows: tensile strength is in accordance with GB / T 1040-2006; elongation at break is in accordance with GB / T 1040-2006; flexural strength is in accordance with GB / T 1040-2008; flexural modulus is in accordance with GB / T1040-2008; cantilever beam impact strength is in accordance with GB / T1843-2008; flame retardant grade is in accordance with "Flammability UL94 Grade" to test the flame retardant grade of high-strength flame-retardant nylon material. The test results are shown in Table 1:

[0165] Table 1

[0166]

[0167] Comparative Example 1 replaces the modified glass fiber in Example 1 with E-glass fiber. The test results show that the modified glass fiber prepared by the present invention can improve the problems of strong adhesion and poor fluidity of nylon materials in the molding process and can also effectively improve the mechanical properties of nylon materials. Comparative Example 2 uses nylon 6, which is common in the market, as the preparation raw material, and the mechanical properties are significantly reduced compared with Example 1, indicating that the strong flame retardancy and thermal stability of modified polyamide 4 can be effectively used in nylon materials, and it is one of the very important raw materials in the preparation process of nylon materials.

[0168] 1. Infrared spectrum analysis of modified polyamide 4

[0169] The infrared spectrum of modified polyamide 4 obtained by dissolving the polystyrene matrix is ​​as follows: Figure 2 As shown. Among them, the characteristic absorption peaks at 1538cm-1 and 1650cm-1 are respectively attributed to the vibration absorption of amide II band and amide I band. Amide II band contains the stretching vibration of CN and CC and the plane bending vibration of NH. Amide I band is caused by the stretching vibration of C=O and the deformation vibration of CCN; the characteristic peaks at 2872cm-1 and 2949cm-1 are attributed to the symmetric and asymmetric stretching vibration of CH bond in methylene; the broader absorption peak at 3290cm-1 corresponds to the stretching vibration of NH connected by hydrogen bond. In general, changing the dosage ratio of butyrolactam / polystyrene has no obvious change on the infrared spectrum of the product modified polyamide 4.

[0170] 2. X-ray diffraction (XRD) analysis of modified polyamide 4

[0171] Modified polyamide 4 is a polycrystalline polymer, usually with two crystal forms, α and γ. The properties of the α crystal form are relatively stable, and the molecular chains in its crystal region are in a fully extended state, the amide group and the methylene group are in the same plane, and the anti-parallel arrangement between the molecular chains is conducive to the formation of hydrogen bonds. The XRD characterization results of the modified polyamide 4 prepared by the present invention are as follows: Figure 3 As shown. It can be seen that all samples have obvious diffraction characteristic peaks at 20.6° and 24°, corresponding to the (200) and (002, 202) crystal planes of α-crystalline modified polyamide 4, respectively. From the XRD results, it can be seen that for this experimental system, when the raw material ratio is butyrolactam 50 / polystyrene 50 (weight ratio), the diffraction characteristic peak corresponding to the α-crystalline modified polyamide 4 obtained is the strongest, and its peak is narrow, indicating that the grain size is large and the crystallinity is good.

[0172] 3. Thermal stability analysis of modified polyamide 4

[0173] Figure 4 The TGA curve of modified polyamide 4 is shown. Figure 4 It can be seen that the overall weight loss curve can be roughly divided into three temperature ranges: the weight loss at 100-200°C corresponds to the water absorption of the modified polyamide 4 and the residual small amount of butyrolactam monomer. The weight loss curves of the two samples in this stage basically overlap, and the weight loss rates are very low, indicating that the samples can basically remove the residual monomers and moisture after purification; the weight loss of the samples in the temperature range of 200-300°C is more obvious, because the butyrolactam anion polymerization may cause side reactions such as branching in addition to the linear growth of the modified polyamide 4 molecular chain, so the weight loss in this stage can be attributed to the thermal decomposition and breakage of the branch chains in the modified polyamide 4 molecular structure; the weight loss rate in the range of 300-450°C is relatively large, corresponding to the thermal decomposition and breakage of the main chain of the modified polyamide 4 molecule. Figure 4It can be seen that the thermal stability of the modified polyamide 4 obtained in the experimental system with a raw material ratio of butyrolactam 80 / polystyrene 20 (weight ratio) is better than that of the modified polyamide 4 obtained in the experimental system with a raw material ratio of butyrolactam 80 / polystyrene 20 (weight ratio).

[0174] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a high-strength flame-retardant nylon material, characterized in that: The following steps are involved: S1. The modified polyamide 4, initiator, antioxidant were added to a high-speed mixer and mixed at a speed of 350 to 500 r / min for 2 to 5 minutes to obtain a preliminary mixed solution; S2. The preliminary mixed solution obtained in step S1 is added with modified glass fiber, mixed at a speed of 1000 to 1200 r / min for 3 to 5 minutes, and dried at 100 to 120 ° C for 2 to 4 hours to obtain a secondary mixed solution; S3. The mixed solution after drying is pelletized by a twin-screw extruder and dried at 150 to 180 ° C for 2 to 4 hours to obtain high-strength flame-retardant nylon pellets; S4. The high-strength flame-retardant nylon pellets obtained in step S3 are subjected to strip injection molding by an injection molding machine to obtain a high-strength flame-retardant nylon material test sample.

2. The method for preparing a high-strength flame-retardant nylon material according to claim 1, characterized in that: The modified polyamide 4 is prepared by the following steps: S101. Add 15 to 25 parts of butyrolactam and 20 to 30 parts of polystyrene to a three-necked flask, melt at 100 to 130° C. to obtain a uniform mixed solution, and mechanically stir for 1 to 3 hours; S102. Add 1 to 5 parts of 2-chloroethyl ester and 0.5 to 2 parts of 2,3-dichloropropyl ester to the homogeneous mixed solution obtained in step S101, and stir at a speed of 150 to 240 r / min at 75 to 85 ° C; S103. Add 0.5 to 2.0 parts of sodium hydroxide as a catalyst for vacuum distillation to remove water in the experimental system; S104. Add 0.5 to 2.0 parts of toluene-2,4-diisocyanate as an activator, and obtain a modified polyamide 4 / polystyrene composite material by casting; S105. The modified polyamide 4 / polystyrene composite material is crushed, and the polystyrene is washed away with tetrahydrofuran to obtain modified polyamide 4 powder.

3. A high-strength flame-retardant nylon material according to claim 2, characterized in that: In step S103, the pressure of the reduced pressure distillation is 2.33-3.03 kPa, and the temperature is 100-120°C.

4. A high-strength flame-retardant nylon material according to claim 2, characterized in that: In step S104, the casting temperature is 45-55°C and the casting time is 20-24 hours.

5. The high-strength flame-retardant nylon material according to claim 1, characterized in that: The preparation steps of the modified glass fiber are: S201. Add E-glass fiber to deionized water and ultrasonically disperse for 15 to 20 minutes to obtain a glass fiber dispersion; S202. The toughening agent, dimethyl silicone oil and anhydrous ethanol are uniformly mixed to obtain a primary mixed solution; S203. The glass fiber dispersion is added to the primary mixed solution and mechanically stirred for 10 to 15 minutes, and then ultrasonically dispersed for 15 to 20 minutes to obtain a secondary mixed solution; S204. Filter, wash and dry the secondary mixed liquid to obtain modified glass fiber.

6. The high-strength flame-retardant nylon material according to claim 5, characterized in that: The toughening agent is a liquid crystal elastomer.

7. The high-strength flame-retardant nylon material according to claim 5, characterized in that: The mass ratio of the toughening agent, dimethyl silicone oil and anhydrous ethanol is: 2-8: 0.5-3: 20-25.

8. The method for preparing a high-strength flame-retardant nylon material according to claim 1, characterized in that: The initiator is cumene hydroperoxide.

9. The method for preparing a high-strength flame-retardant nylon material according to claim 1, characterized in that: The antioxidant is one or more of 2,6-di-tert-butyl-4-methylphenol, p-phenylenediamine, and didodecanol ester.

10. A high-strength flame-retardant nylon material, obtained according to the preparation method of the high-strength flame-retardant nylon material according to any one of claims 1 to 9, characterized in that: The composition comprises the following components respectively by weight: 50 to 80 parts of modified polyamide 4, 15 to 25 parts of modified glass fiber, 5 to 15 parts of initiator and 1 to 3 parts of antioxidant.